Non-(Re)Translations: A New Perspective on Retranslation Studies - İrem Ceren Doğan ([sic])
In recent years, scholarly discourse has extensively examined retranslations, yet non-retranslations have received insufficient attention. The term non-retranslations refers to works in translation that persist in a literary system without undergoing retranslation. This study examines a concise bibliography of non-retranslations to gain a better understaning of the idea and its dynamics within the Turkish literary system. The bibliography of nineteen works by five Nobel laureates examines instances of non-retranslation through Antoine Berman’s notion of “great” translators. Another key notion used in this study is that of non-translation, which is also explored in the works of six modernist authors. Debates on the lack of (re)translation are compared to the significant increase in retranslations during the 2000s. This study’s findings reflect a tendendy that within the translated literary system Türkiye, non-translations and non-retranslations coexist alongside retranslations.Keywords: non-retranslation, non-translation, retranslation, great translation